2023
DOI: 10.1001/jamanetworkopen.2023.32556
|View full text |Cite
|
Sign up to set email alerts
|

Video Intervention and Goals-of-Care Documentation in Hospitalized Older Adults

Angelo E. Volandes,
Sophia N. Zupanc,
Joshua R. Lakin
et al.

Abstract: ImportanceDespite the benefits of goals-of-care (GOC) communication, many hospitalized individuals never communicate their goals or preferences to clinicians.ObjectiveTo assess whether a GOC video intervention delivered by palliative care educators (PCEs) increased the rate of GOC documentation.Design, Setting, and ParticipantsThis pragmatic, stepped-wedge cluster randomized clinical trial included patients aged 65 years or older admitted to 1 of 14 units at 2 urban hospitals in New York and Boston from July 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Across the 3 patient cohorts, we observed low-value care in 7627 of the 37 116 control patient-months (20.5%) and 7416 of the 46 381 intervention patient-months (16.0%) (Table 2 and Figure 3). Overall, 554 patients in the diabetes cohort (20.7%), 1362 patients in the insomnia/anxiety cohort (32.2%), and 143 patients in the prostate cancer screening cohort (6.1%) received low-value care.…”
Section: Resultsmentioning
confidence: 98%
“…Across the 3 patient cohorts, we observed low-value care in 7627 of the 37 116 control patient-months (20.5%) and 7416 of the 46 381 intervention patient-months (16.0%) (Table 2 and Figure 3). Overall, 554 patients in the diabetes cohort (20.7%), 1362 patients in the insomnia/anxiety cohort (32.2%), and 143 patients in the prostate cancer screening cohort (6.1%) received low-value care.…”
Section: Resultsmentioning
confidence: 98%
“…A study of video intervention and documentation of goals of care found that documentation was greater in the intervention group than in the control group [ 15 ]. The 2x2 contingency table was (3744, 2279, 2396, 2383), with a p-value of < 0.001 by Fisher’s exact.…”
Section: Resultsmentioning
confidence: 99%
“…A study of minimally invasive surfactant therapy (MIST) in preterm infants found that hospitalization in the first two years was 25.1% in the MIST group and 38.2% in the control group [14]. A study of video intervention and documentation of goals of care found that documentation was greater in the intervention group than in the control group [15]. The 2x2 contingency table was (3744, 2279, 2396, 2383), with a p-value of < 0.001 by Fisher's exact.…”
Section: Case Studiesmentioning
confidence: 99%